SPATIAL DISTRIBUTION OF WILLINGNESS TO PAY FOR HEALTH SERVICES OF HOUSEHOLDS IN POLAND - Jewczak, Maciej (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The purpose of this article is to demonstrate the spatial distribution of willingness to pay for health services of households in Poland, on the example of voluntary health insurance. With the ability to identify a household in the databases of the Social Diagnosis, on the basis of which the research was conducted and with the use of multivariate analysis techniques, the article indicates the similarities in household structure in terms of the willingness to pay, as well as the socio-economic factors.